Discontinuous Galerkin approximations for near-incompressible and near-inextensible transversely isotropic bodies. (1st April 2020) - Grieshaber, B.J.; Rasolofoson, F.; Reddy, B.D.
Abstract: This work studies discontinuous Galerkin (DG) approximations of the boundary value problem for homogeneous transversely isotropic linear elastic bodies. Low-order approximations on triangles are adopted, with the use of three interior penalty DG methods, viz. nonsymmetric, symmetric and incomplete. It is known that these methods are uniformly convergent in the incompressible limit for the isotropic case. This work focuses on behaviour in the inextensible limit for transverse isotropy. An error estimate suggests the possibility of extensional locking, a feature that is confirmed by numerical experiments. Under-integration of the extensional edge terms is proposed as a remedy. This modification is shown to lead to an error estimate that is consistent with locking-free behaviour. Numerical tests confirm the uniformly convergent behaviour, at an optimal rate, of the under-integrated scheme.